Effect of metformin and rosiglitazone on lipid metabolism in HIV infected patients receiving protease inhibitor containing HAART - Tomažič, Janez (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Aims. Insulin resistance may be the primary event in the protease inhibitor-associated metabolic syndrome. Treatment with insulin sensitizers (metformin, rosiglitazone) can ameliorate insulin resistance. So far, the effects of these agents on blood lipids have not been well determined. The aimof the present study was to evaluate the effects of metformin and rosiglitazone treatment on lipid metabolism in HIV infected patients receivingprotease inhibitors containing HAART. Design and Methods. HIV infected male patients (>18 years) were eligible for the study if they had impaired glucose tolerance with insulin resistance, characterized by fasting insulin concentration greater then 20 mIU/L and if they were on stable antiretroviral therapy regimen including a protease inhibitor for at least 12 months prior to the study enrolment. The patients were randomly assigned to receive either 1 g/day metformin (metformin group, n=30) or 4 mg/day rosiglitazone maleate (rosiglitazone group, n=30) or no treatment (control group, n=30). The primary efficacy parameters were fasting plasma lipids, glucose levels and fasting insulin levels compared between baseline and week 48, by treatment groups. Results. The total cholesterol concentration in rosiglitazone group increased from 5.76+-7.1+-1.6 mmol/l (23% increase, p<0.05), HDL levels increased from 0.91+-0.44 to 1.3+-0.2 (38% increase, p<0.01) and LDL levels increased from 3.5+-0.98 to 4.5+-1.0 (28% increase, p<0.05). Treatment with metformin had no significant effect on total, HDL and LDL cholesterol. After 48 weeks of treatment, the fasting triglycerides concentration in the metformin group declined from 4.1+-1.6 to 3.2+-1.3 mmol/l(22% decrease, p<0.05) but in the rosiglitazone group no statistically significant effect on plasma triglycerides was noted. (Abstract truncated at 2000 characters)
Keywords: Anti-Hiv Agents; Blood; CD4 limfociti, štetje; Cd4 Lymphocyte Count; Cholesterol; Drug Therapy; Glucose Tolerance Test; Glukoza, tolerančni test; HIV; Hiv Infections; HIV infekcije; Holesterol; Insulin; Insulin Resistance; Insulinska rezistenca; Inzulin; Lipoproteini, HDL, holesterol; Lipoproteini, LDL, holesterol; Lipoproteins, Hdl Cholesterol; Lipoproteins, Ldl Cholesterol; Metformin; proteazni inhibitorji; Proti-HIV zdravila; serumski lipidi; therapy; Trigliceridi; Triglycerides; zdravljenje